ginny1029

05-31-2009, 01:06 PM

the instructions are solve by completing the square

the problem reads

2x^2 + 6x -56 = 0

i divide everything by 2 to get the x by itself and move the -56

2x^/2 + 6x/2_______ = 56/2

i now have

x^2 + 3x _______ = 28

i divide the 3 by 1/2 and get 3/2 and square it and get 9/4

x^2 + 3x + 9/4 = 28 + 9/4

i change the 28 to fourths and get

x^2 + 3x + 9/4 = 112/4 + 9/4

x^2 + 3x + 9/4 = 121/4

this becomes

(x + 3/2)^2 = 121/4

does this look right so far?

the problem reads

2x^2 + 6x -56 = 0

i divide everything by 2 to get the x by itself and move the -56

2x^/2 + 6x/2_______ = 56/2

i now have

x^2 + 3x _______ = 28

i divide the 3 by 1/2 and get 3/2 and square it and get 9/4

x^2 + 3x + 9/4 = 28 + 9/4

i change the 28 to fourths and get

x^2 + 3x + 9/4 = 112/4 + 9/4

x^2 + 3x + 9/4 = 121/4

this becomes

(x + 3/2)^2 = 121/4

does this look right so far?